PERKEMBANGAN AWAL PERADILAN ISLAM (STUDI TENTANG PENERAPAN PRINSIP-PRINSIP NEGARA HUKUM) - Abdul Hafiz (Universitas Islam Negeri Fatmawati Sukarno, 2015)
Muslim cummunity is a part of world communities who dream rechtstaat or rule of law. The politic philosophers or experties have different opinions about principles which contained by rule of law concept. Islam, as the religion with it’s doctrins on law, has distinguish concept of rule of law. Islamic rule of law is a variant of rule of law concepts. After studying some literatures, it is founded that Islamic rule of law has some principles: adherence, faith, equality, honouring the human right, and judge independency.